Effects of Sport Climbing on Multiple Sclerosis - Steimer, Julia; Weissert, Robert (Frontiers in Physiology, 2017)
Multiple sclerosis (MS) is an autoimmune and neurodegenerative disease of the central nervous system (CNS) with different types of disease courses (relapsing-remitting, secondary-progressive, primary progressive) that leads to physical as well as mental disability. The symptoms comprise paresis or/and paralysis, ataxia, bladder dysfunction, visual problems as well as effects on cognition. There is limited data regarding the possible effects of sports climbing respectively therapeutic climbing on patients with MS. Sports’ climbing offers many potentially beneficial effects for patients with MS since there are effects on coordination, muscular strength and cognition to name the most relevant ones. Also, disease models in rodents point towards such positive outcomes of climbing. Therefore, we assessed the currently available research literature on general effects of physical exercise, impact of climbing on body and mind and therapeutic climbing for prevention or therapy for the treatment of MS. The sparse published controlled trials that investigated this sports activity on different groups of patients with neurological or geriatric diseases grossly differ in study design and outcome parameters. Nevertheless, it appears that climbing offers the opportunity to improve some of the symptoms of patients with MS and can contribute to an enhanced quality of life.